Deep Lymphatics of the Spleen - Fukuda, Takao (The Tohoku Journal of Experimental Medicine, 1963)
Two efferent lymphatic currents were confirmed in the present study: (1) Perivenous, which originated from the subintimal spaces of the veins, and (2) periarterial, which started from the follicles. No afferent currents were detected. Evidence is still required to clarify the problem, whether the splenic blood circulation is of a closed or open type. Splenic lymphatics should be investigated in reference to the aspect of splenic blood circulation. Die Existenz von tief-liegenden Lymphwegen der menschlichen Milz wurde betont. Es waren zwei Systeme von abführenden Lymphwegen: (1) perivenöses and (2) periarteriales System. Nirgends wurden zuführende Lymphwege entdeckt. Der Zusammenhang zwischen Blut- und Lymph-zirkulation wurde zugleich cliskutiert.